Non-image Forming Light Detection by Melanopsin, Rhodopsin, and Long-Middlewave (L/W) Cone Opsin in the Subterranean Blind Mole Rat, Spalax Ehrenbergi: Immunohistochemical Characterization, Distribution, and Connectivity - Esquiva, Gema; Avivi, Aaron; Hannibal, Jens (Frontiers in Neuroanatomy, 2016)
The blind mole rat, Spalax ehrenbergi, can, despite severely degenerated eyes covered by fur, entrain to the daily light/dark cycle and adapt to seasonal changes due to an intact circadian timing system. The present study demonstrates that the Spalax retina contains a photoreceptor layer, an outer nuclear layer (ONL), an outer plexiform layer (OPL), an inner nuclear layer (INL), an inner plexiform layer (IPL) and a ganglion cell layer (GCL). By immunohistochemistry, the number of melanopsin (mRGCs) and non-melanopsin bearing retinal ganglion cells was analyzed in detail. Using the ganglion cell marker RNA-binding protein with multiple splicing (RBPMS) it was shown that the Spalax eye contains 890±62 RGCs. Of these, 87 % (752±40) contain melanopsin (cell density 788 melanopsin RGCs/mm2). The remaining RGCs were shown to co-store Brn3a and calretinin. The melanopsin cells were located mainly in the GCL with projections forming two dendritic plexuses located in the inner part of the IPL and in the OPL. Few melanopsin dendrites were also found in the ONL. The Spalax retina is rich in rhodopsin and long/middle wave (L/M) cone opsin bearing photoreceptor cells. By using Ctbp2 as a marker for ribbon synapses, both rods and L/M cone ribbons containing pedicles in the OPL were found in close apposition with melanopsin dendrites in the outer plexus suggesting direct synaptic contact. A subset of cone bipolar cells and all photoreceptor cells contain recoverin while a subset of bipolar and amacrine cells contain calretinin. The calretinin expressing amacrine cells seemed to form synaptic contacts with rhodopsin containing photoreceptor cells in the OPL and contacts with melanopsin cell bodies and dendrites in the IPL. The study demonstrates the complex retinal circuitry used by the Spalax to detect light, and provides evidence for both melanopsin and non-melanopsin projecting pathways to the brain.